S47 Enhanced Il-6/ccl3 Signalling In The Plasma Of Patients With Copd. (10th November 2014) - Ravi, AK; Khurana, S; Banyard, A; Plumb, J; Booth, G; Catley, M; Healy, L; Smith, E; Vestbo, J; Singh, D
Abstract : Rationale: IL-6 is a pro-inflammatory cytokine that signals through soluble (sIL-6R/sgp80) and membrane bound (gp80) receptors to promote recruitment of mononuclear cells. IL-6 induces expression of CCL3, a monocytic chemokine. Monocytes are precursors of macrophages and dendritic cells. They can be classified into three subtypes according to surface expression of CD14 (LPS receptor) and CD16 (FcgammaRIII): CD14++CD16-, CD14+CD16+, CD14-CD16++. We measured plasma levels of IL-6, sIL-6R and CCL3 and determined the chemokine receptor expression profile of circulating monocytes in COPD. Methods: 70 COPD patients and 30 healthy controls comprising 15 smokers (S) and 15 healthy non-smokers (HNS) underwent plasma sampling. Levels of IL-6, sIL-6R and CCL3 were determined by multiplex analysis (MSD) of plasma. Multi-colour flow cytometry was performed on whole blood obtained from 32 COPD patients, 8 S and 8 HNS to measure surface expression levels of chemokine receptors CCR1, CCR2, CCR7, CXCR1 and CX3CR1 on CD14++CD16-, CD14+CD16+ and CD14-CD16++ monocytes. Results: COPD patients had the greatest levels of IL-6 and sIL-6R. CCL3 was not detected in any controls, but was present in a subset of COPD patients.% surface expression of the CCL3 receptor CCR1 measured on CD14++CD16- monocytes of COPD patients was greater than those of HNS (p = 0.04). There were no significant differences in expression levels of other chemokine receptors. Conclusion: We report evidence of enhanced IL-6 signalling in the plasma of COPD patients and increased plasma CCL3 in a subset of individuals from this disease group. Furthermore, there was increased CCR1 expression on COPD monocytes. Enhanced IL-6 may co-ordinate the mononuclear component of the inflammatory response in COPD.